1997
DOI: 10.1016/s0041-1345(96)00550-7
|View full text |Cite
|
Sign up to set email alerts
|

Chimerism, graft-vs-host disease, rejection, and their association with reciprocal donor-host immune reactions after cell, organ, and composite tissue transplantation

Abstract: We have postulated that a small number of donor-derived leukocytes and the recipient immune system mutually interact and reciprocally attenuate both host-vs-graft (HVG) and graft-vs-host (GVH) reactions.1 Multiple cell and organ transplant models confirm the coexistence of donor cell traffiking and graft acceptance.2 However, the outcome of GVH and HVG reactions after drug discontinuation remains unpredictable. In this study, we hypothesize that both the graft's antigenicity and migratory cell load playa deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…20 In a hindlimb LEW-to-BN VCA model, administration of FK506 for 28 and 100 days elicited transient GvHD, followed by rejection and chronic rejection, respectively. 21 The in vitro mixed lymphocyte reaction showed that LEW responders presented a stronger proliferative response to BN stimulators compared with the BN responders to LEW stimulators, 22 which may be one explanation for the relatively higher occurrence of GvHD in the LEW-to-BN combination than in the BN-to-LEW combination.…”
Section: Discussionmentioning
confidence: 99%
“…20 In a hindlimb LEW-to-BN VCA model, administration of FK506 for 28 and 100 days elicited transient GvHD, followed by rejection and chronic rejection, respectively. 21 The in vitro mixed lymphocyte reaction showed that LEW responders presented a stronger proliferative response to BN stimulators compared with the BN responders to LEW stimulators, 22 which may be one explanation for the relatively higher occurrence of GvHD in the LEW-to-BN combination than in the BN-to-LEW combination.…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to consider the higher weight and strength of Lewis rats compared with BN rats of the same age, which are more labile and vulnerable, which is crucial to know when planning a difficult postoperative period. Based on previous studies, Ye et al described a similar GVHD model with ACI-Lewis combination rats, although they also did not provide details [76,[78][79][80][81][82][83].…”
Section: Rat Strainmentioning
confidence: 99%
“…8,29 However, the relevance of overall multlineage chimerism itself has been debated. 30,31 Coexistence of donor-derived and recipient-derived lymphatic populations (chimerism) might be the cause of tolerance or just an effect, an epiphenomenon. 32 In other words, the conditioning regimen might favor the survival of a limited number of regulatory cells such as CD4þ CD25þ T lymphocytes.…”
Section: Skin Grafts and Assessment Of Chimerismmentioning
confidence: 99%